Price and Income Elasticity of Indian Exports-The Role of Supply-Side Bottlenecks - Raissi, Mehdi (IMF Working Papers; Working Paper ;, 2015)
This paper estimates the short-term and long-run price and income elasticity of Indian exports, and investigates the role of supply-side bottlenecks in shaping India's export demand relationship. We use disaggregated export volume data for 45 Indian industries over the period 1990-2013, as well as industry-specific international relative prices, for estimation. Our results indicate that Indian exports are sensitive to international relative-price competitiveness, world demand, and energy shortages. In addition, binding supply-side constraints (notably energy shortages) dampen price responsiveness in the short-term.